Inhibition of ferroptosis alleviates high-power microwave-induced myocardial injury - Wang, Yu; Lu, Yan; Chen, Wen; Xie, Xiaohua (Frontiers in Cardiovascular Medicine, 2023)
Background The use of high-power microwave (HPM) in our daily live is becoming more and more widespread, but the safety has also caused our concern. And ferroptosis is a newly discovered modality that can regulate cell death in recent years. The aim of our study was to demonstrate whether ferroptosis is an important cause of myocardial injury caused by HPM. And whether myocardial injury caused by HPM can be alleviated by inhibiting ferroptosis. Methods We verified the extent of myocardial damage by different doses of HPM through in vivo and in vitro assays, respectively. In addition, GPX4 was knocked down and overexpressed in cardiac myocytes to verify the altered sensitivity of cardiac myocytes to HPM. Finally, the therapeutic effect of Fer-1 and tanshinoneIIA on myocardial injury caused by HPM was verified in in vivo and in vitro assays. Results We found that cardiac tissue and cardiomyocyte injury in mice gradually increased with increasing HPM dose, while ferroptosis markers were consistent with the injury trend. Gpx4 had an important role in ferroptosis in cardiomyocytes caused by HPM. Finally, tanshinoneIIA and Fer-1 could attenuate the damage of cardiac tissues and cardiomyocytes caused by HPM. Conclusions In conclusion, our study found that ferroptosis, a novel mode of cell death, is present in myocardial injury caused by HPM. Moreover, tanshinone, a drug already in clinical use, can significantly reduce myocardial injury caused by HPM, which is promising to provide new therapeutic ideas for myocardial injury caused by HPM.